RARE FORMS OF UTERINE LEIOMYOMAS (description of a case) - Yu. G. Payanidi; K. I. Zhordania; I. S. Stilidi; T. I. Zakharova; V. Yu. Bokhyan (IRBIS LLC, 2017)
Leiomyomas predominate among benign nonepithelial tumors of the corpus uteri. Leiomyoma is commonly an asymptomatic tumor and detectable in most cases at routine gynecological examinations. However, some forms of leiomyomas have a definite metastatic potential and, despite its benign morphological signs, may metastasize to the lung. Fatal cases resulting from tumor spread along the postcava to the right atrium are described.